(untitled) (Research, Society and Development, 2024)
Direct composite veneers have become an increasingly popular option for the esthetic and functional restoration of compromised anterior teeth. This scientific study offers a comprehensive review of this restorative technique, exploring twenty essential theoretical bases for its understanding and effective application. The objective of this study is to present a review of material properties, application techniques and technological advances associated with composite resin veneers. Proper aesthetic planning is essential for predictable results, and we address aspects such as facial analysis, shade selection and diagnostic mock-ups. The advantages of composite resin veneers, and conservation of tooth structure and affordability, as well as addressing their disadvantages and limitations, longevity considerations and complex case management strategies. Since, economic, ethical, legal issues and recent technological advances and future prospects. In this way, composite resin veneers continue to play an important role in aesthetic dentistry, offering an effective and reliable solution for improving the aesthetics of the smile. With a comprehensive understanding of the theoretical and practical evidence related to this topic, dental professionals are well equipped to offer high-quality treatments that meet patients’ needs and expectations, and are expanding their knowledge of the technique in order to achieve greater success, guaranteeing satisfactory aesthetic and functional results.